Preparing Teacher Candidates to be "Effective" in the Classroom: Lessons Learned from National Teachers of the Year. Issue 1 (4th March 2019) - Greathouse, Paula; Eisenbach, Brooke B.; Kaywell, Joan F.
Abstract: Defining what it means to be an "effective teacher" is a difficult, but necessary, undertaking, as research reveals a correlation between teacher qualities and student success (Buchel and Edwards2005 ; Darling-Hammond2000 ; Lupascu, Pânisoa, and Pânisoar 2014; Stronge2007 ). The literature on this topic clearly demonstrates that there is no consensus on exactly what traits and characteristics truly define an effective teacher. Given this lack of agreement, the question for teacher educators becomes how do we prepare teacher candidates to be effective in the classroom when researchers, policymakers, and administrators can't agree on the traits that encompass what the system has come to deem an "effective" teacher ? Throughout this article, we share our findings from an exploratory case study of National Teachers of the Year. Through an analysis of personal teacher of the year narratives and nomination letters, we learned that even in the ever-changing world of education, specific characteristics and philosophies which support and exemplify outstanding teaching have remained constant over the years. Award winning educators agree that teacher effectiveness is realized only through the intersection of curriculum, relationships, collaboration, engagement, and a commitment to further one's learning. In this article, we offer insight into each of these ideological constants and discuss the implications they have for today's teacher education programs.